Measuring structural inhomogeneity of a helical conjugated polymer at high pressure and temperature. Issue 7 (12th February 2019) - Arge, Tummas Napoleon; Konôpková, Zuzana; Haase, Dörthe; Liermann, Hanns‐Peter; Scherf, Ullrich; Guha, Suchismita; Knaapila, Matti
ABSTRACT: We report on X‐ray scattering measurements of helical poly[9, 9‐bis(2‐ethylhexyl)‐fluorene‐2, 7‐diyl] by mapping the sample with 10 μm spatial resolution from 0.3 GPa to 36 GPa. We follow the strongest 00 l reflection, which moves toward higher scattering angles with pressure indicating planarization of helical polyfluorene. Lateral inhomogeneity is increased for >10 GPa concomitant with the solidification of the pressure transmitting medium (a 4:1 mixture of methanol and ethanol). We also follow the 00 l reflection with increasing temperature at the constant pressure of 4.3 GPa in neon. We observe a sharp shift toward higher scattering angles indicative of a phase transition at 167–176 °C. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 392–396 Abstract : X‐ray scattering data from polyfluorene polymer is collected by mapping the sample with 10 μm spatial resolution from 0.3 GPa to 36 GPa. The structural inhomogeneity is characterized. The data are also collected with increasing temperature at 4.3 GPa. A phase transtion is identified at about 170°C.